From trauma to resilience: advancing cultural responsiveness and equity in the Muskowekwan First Nation’s healing journey - Sasakamoose, JoLee; Pete, Shauneen; O’Soup, Fred; Wolfe, Tiffany (Frontiers in Public Health, 2024)
Introduction: Introduction: The Muskowekwan First Nation (MFN) in Saskatchewan, Canada, epitomizes the enduring strength and cultural preservation of the Saulteaux people. This community faces the lasting effects of colonial trauma, especially the violence, abuse, and adversity experienced by students at the Muskowequan Indian Residential School (MIRS). Decades of abuse by institutional leaders caused generational trauma, contributing to current mental health and well-being challenges. This study highlights the community's role in sharing experiences and shaping healing processes to develop the MFN Family Healing and Wellness Centre in response to urgent community concerns. It examines the integration of Justice, Diversity, Equity, and Inclusion (J-DEI) principles and cultural responsiveness in fostering community resilience and mental well-being. Methods: Adopting a community-based participatory research framework, this study employs a mixed-methods approach, including community engagement sessions and surveys. Collaborating closely with the MFN leadership, it draws upon the specialized expertise of Author2 and Author1, leaders in Indigenous health and research. The research uses qualitative and quantitative data collection, emphasizing the importance of community input and leadership in shaping the research process and outcomes. Results: Findings emphasize the community's commitment to spiritual and cultural practices as vital healing components. Amidst the heightened awareness of the lingering effects of the MIRS within the MFN community, these insights informed the development of the Centre, ensuring it incorporates the community's desires for culturally relevant healing practices. The grand opening of Phase I of the Centre in February 2023 emerged as a significant step forward, symbolizing a move towards holistic community health that honors resilience, holistic wellness, and cultural continuity. Discussion: This case study contributes to the literature on integrated, culturally responsive